Marriage Problems and Resolution Strategies: A Case Study of Married Couples with Under Ten Years of Marriage in 2024 - Ningsih, Eka Prihatin; Rahmawat, Siti Nur (Jurnal Indonesia Sosial Sains, 2025)
Marriage is a social institution that often faces various challenges, especially for couples with a marriage age under ten years old. This research aims to identify common problems faced by married couples in the early stages of marriage and explore strategies to solve them. The research method used was a case study with a qualitative approach through in-depth interviews and observations on several couples with a marriage age of 1–10 years. The results of the study show that the most common problems that arise include less effective communication, differences in child parenting, financial management, and adjustment of roles and expectations in the household. Effective resolution strategies include improving communication skills, conflict management, strengthening emotional support, as well as involvement in marriage counseling. This study recommends the importance of pre-marriage education and ongoing mentoring for young couples to minimize the risk of conflict and improve the quality of marital relationships.